Benin : Request for a Three-year Arrangement Under the Extended Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Benin. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2017)
This paper discusses Benin's Request for a Three-Year Arrangement under the Extended Credit Facility. The new program aims to create fiscal space by stepping up domestic revenue mobilization and enhancing the efficiency of government spending; gradually increasing absorptive capacity to scale up investment; strengthening public debt management; and promoting private sector investment through stronger institutions and a better business environment while keeping debt sustainable. It will also aim to ensure that scaled-up public investment is consistent with debt sustainability. This is particularly important for Benin: recent borrowing has significantly reduced available fiscal space, and potential risks have materialized as a result of growth shortfalls, fiscal slippages, and contingent liabilities from state-owned enterprises.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet